Fast Dissolving Sublingual Strips: A Novel Approach for the Delivery of Isosorbide Dinitrate - Marzieh Fathei; Mitra Alami-milani; Sara Salatin; Sharahm Sattari; Hassan Montazam; Farhad Fekrat; Mitra Jelvehgari (Tabriz University of Medical Sciences, 2019)
Background: Isosorbide dinitrate (ISDN) is used for treating the angina attacks. In addition, oral ISDN is available in immediate and sustained release formulations and the bioavailability of ISDN is about 20-25% when taken orally. Further, the ISDN films are developed for sublingual drug delivery by improving drug bioavailability. The present study aimed to design and evaluate the physicochemical properties of the film formulation for sublingual delivery of ISDN. Methods: In the present study, sublingual films were prepared by the solvent casting technique using the hydroxypropyl methylcellulose (HPMC) polymers (i.e., 100, 150 and 200 mg) with a different drug to polymer ratios (i.e., 1:5, 1:7.5 and 1:10). Then, ISDN was evaluated for the film appearance, drug content, surface pH, mucoadhesion force, differential scanning calorimetry (DSC), in vitro drug release, and ex vivo permeability. Results: Based on the results, F3 formulation (1:10 ISDN to HPMC ratio) showed acceptable thickness (0.93 mm), weight (11.14 mg), surface pH (7.82), moisture absorption capacity (6.08%), elasticity (>200), mucoadhesion force (18.05 N/cm2), and drug content (6.22%). Furthermore, the results demonstrated that HPMC polymer improved the characteristics of the films, modified the bioadhesiveness, and finally, enhanced elasticity. However, DSC thermogram failed to show any crystalline drug substance in the films except for F1 (immediate release) and the endothermic peak of ISDN was absent in F2 and F3 films. Therefore, the drug which was entrapped into the film was in an amorphous or disturbed-crystalline phase of the molecular dispersion or dissolved in the melted polymer in the polymeric matrix. Moreover, the drug release from the films was faster compared to the tablet® (P<0.05). Conclusion: In general, the formulation of F1 was observed to be an appropriate candidate for developing the sublingual film for the remedial use.